The Impact of Islamic Banking on Redistribution of Sustainable Income - Yusuf, Jamiu Adeniyi; Mumini Oladapo, Rauf; Ismail, Ayuba Aderole; Tunde, Muhammed Azeem (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Islamic banking operates within a framework guided by Shariah principles, emphasizing fairness, equity, and social justice. Unlike conventional banking systems that rely on interest-based transactions, Islamic banking prohibits riba (interest) and promotes profit-and-loss sharing. However, income inequality remains a persistent challenge in many Muslim-majority countries, raising questions about how Islamic banking can contribute to sustainable income redistribution. This study employs primary data collected from 400 respondents across four countries where Islamic banking operates: Saudi Arabia, Malaysia, Indonesia, and Nigeria, with 100 participants sampled per country. Data were gathered using structured interviews and analyzed using qualitative and quantitative approaches, supported by a review of literature and case studies. The findings reveal that Islamic banking significantly contributes to wealth redistribution and economic justice through instruments such as zakat, waqf (endowments), and profit-sharing models. The research concludes that Islamic banking is not only a viable alternative to conventional systems but also an essential mechanism for achieving sustainable income redistribution. These findings have significant implications for policymakers, financial institutions, and communities seeking to address income inequality and foster a more equitable economic system.